2021
DOI: 10.1038/s12276-021-00689-6
|View full text |Cite
|
Sign up to set email alerts
|

Thrap3 promotes R-loop resolution via interaction with methylated DDX5

Abstract: Transcription-replication conflicts lead to DNA damage and genomic instability, which are closely related to human diseases. A major source of these conflicts is the formation of R-loops, which consist of an RNA-DNA hybrid and a displaced single-stranded DNA. Although these structures have been studied, many aspects of R-loop biology and R-loop-mediated genome instability remain unclear. Here, we demonstrate that thyroid hormone receptor-associated protein 3 (Thrap3) plays a critical role in regulating R-loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Before our study, it was known that the ATP-dependent RNA helicase DDX5, a member of the DEAD box (Asp-Glu-Ala-Asp [DEAD]) protein family, unwinds RNA-RNA and RNA-DNA duplexes (Hirling et al, 1989;Rossler et al, 2001;Xing et al, 2017) and is an important player in RNA metabolic processes involving structured RNAs (Buszczak and Spradling, 2006;Cloutier et al, 2012;Fuller-Pace, 2013;Xing et al, 2017). Although DDX5 can resolve G-quadruplex structures (Wu et al, 2019), it is primarily known as a key factor in R-loop homeostasis Kang et al, 2021;Kim et al, 2020;Mersaoui et al, 2019;Sessa et al, 2021;Villarreal et al, 2020;Yu et al, 2020). Dbp2, the yeast homolog of DDX5, resolves the RNA-DNA hybrids of R-loops (Cloutier et al, 2012) and its human counterpart DDX5 also resolves R-loops both in vitro and in vivo (Mersaoui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before our study, it was known that the ATP-dependent RNA helicase DDX5, a member of the DEAD box (Asp-Glu-Ala-Asp [DEAD]) protein family, unwinds RNA-RNA and RNA-DNA duplexes (Hirling et al, 1989;Rossler et al, 2001;Xing et al, 2017) and is an important player in RNA metabolic processes involving structured RNAs (Buszczak and Spradling, 2006;Cloutier et al, 2012;Fuller-Pace, 2013;Xing et al, 2017). Although DDX5 can resolve G-quadruplex structures (Wu et al, 2019), it is primarily known as a key factor in R-loop homeostasis Kang et al, 2021;Kim et al, 2020;Mersaoui et al, 2019;Sessa et al, 2021;Villarreal et al, 2020;Yu et al, 2020). Dbp2, the yeast homolog of DDX5, resolves the RNA-DNA hybrids of R-loops (Cloutier et al, 2012) and its human counterpart DDX5 also resolves R-loops both in vitro and in vivo (Mersaoui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DDX5 can also resolve R-loops at DNA DSBs (Yu et al, 2020). Although human DDX5 is known to work with several proteins, including ATAD5, BRCA2, Thrap3 (Gomez-Gonzalez and Aguilera, 2021; Kang et al, 2021;Kim et al, 2020;Sessa et al, 2021), it was not known to associate with human topoisomerases in the context of R-loops, except for a recent study showing that Drosophila p68 (homolog of DDX5) interacts with Top3b-TDRD3 as a part of RNAi machinery and promotes heterochromatin formation (Lee et al, 2018). Our study provides evidence for an epistatic role of TOP3B and DDX5 in R-loop resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Why restoring DDX5 expression in hypoxia leads to further R-loop accumulation above the level observed in hypoxia is unclear. Previous reports have all shown that expression of DDX5 leads to R-loop resolution i.e., a decrease in R-loop levels [15][16][17][18][19] . To our knowledge, expression of DDX5 in hypoxia is the first example of a context where DDX5 has been linked to R-loop accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Methylated DDX5 recruits exonuclease XRN2 and degrades R-loops in the transcription termination region downstream of the poly(A) site to promote the release of RNA polymerase II, thus promoting smooth transcription ( 61 ). In this process, thyroid hormone receptor-associated protein 3 (Thrap3) binds to methylated DDX5 to promote the recruitment of XRN2 to R-loops ( 62 ). BRCA2 is a DSB repair factor.…”
Section: Involvement Of Ddx5/ddx17 In Rna Metabolism and Cancer Devel...mentioning
confidence: 99%